The Effect of Budget Management Quality and Internal Audit to Financial Statement Quality in the Ministries and Agencies - Inayattulloh, Muhammad Ramdhan; Siswantoro, Dodik (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2019)
The government’s financial statement represents the state’s financial management accountability. This research aims to analyze the factors that influence the quality of the state’s financial statement using the variables of the state’s budget management quality and internal audit. This research observed 52 data that covered the period of 2015 – 2017 using the multiple linear regression analysis based on data panel. The variable also uses control variable to analyze data properly such as size and work unit. Results of the research suggest that the budget management quality and internal audit has a positive effect on the central government’s financial statement quality. This is also supported by correlation test of Pearson. Each ministry and agency should be empowered the budget management quality and internal audit to support the financial statement quality in ministries and agencies. As public sector institution control of budget should be the main concern to create good financial statement quality. This may the first paper which analyze factors of budget management quality and internal audit to financial statement quality in ministries and agencies. Research in public sector especially for government is rare as the data may not be available.